2014
DOI: 10.1002/2014ja020509
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for the core field polarity of magnetic flux ropes against the reconnection guide field

Abstract: We present the observational evidence by Time History of Events and Macroscale Interactions during Substorms (THEMIS)-D spacecraft to demonstrate that magnetic flux rope can have a core field polarity opposite to the guide field during asymmetric reconnection with a high magnetic shear across the magnetopause. In the presented event, a bipolar reconnection outflow was observed at the magnetopause, across which the magnetic shear was~149°corresponding to a predicted guide field B G = À15.6 nT. The ratios for ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 23 publications
1
5
0
Order By: Relevance
“…Thus, we conclude that the core field for most of the identified flux ropes is produced due to the IMF B y . Apparently, this conclusion is inconsistent with the previous result where they found that the core field is created due to the ambient Hall magnetic field [ Eastwood et al , ; Teh et al , , ; C. Huang et al , ; S. Y. Huang et al , ; Wang et al , ]. In these papers, they all focused on the secondary flux ropes.…”
Section: Discussion and Summarymentioning
confidence: 80%
See 1 more Smart Citation
“…Thus, we conclude that the core field for most of the identified flux ropes is produced due to the IMF B y . Apparently, this conclusion is inconsistent with the previous result where they found that the core field is created due to the ambient Hall magnetic field [ Eastwood et al , ; Teh et al , , ; C. Huang et al , ; S. Y. Huang et al , ; Wang et al , ]. In these papers, they all focused on the secondary flux ropes.…”
Section: Discussion and Summarymentioning
confidence: 80%
“…The case study shows the correlation between the core field and the interplanetary magnetic field (IMF) and concluded that the core field of the flux rope in the magnetotail originates from the IMF B y [ Nakamura et al , ]. However, recent observation found that the core field of the secondary magnetic flux rope was created due to the compression of the ambient Hall magnetic field [ Eastwood et al , ; C. Huang et al , ; S. Y. Huang et al , ; Teh et al , , ; Wang et al , ]. Figure show the scatterplot of the core fields of the flux ropes versus the IMF B y .…”
Section: Discussion and Summarymentioning
confidence: 99%
“…(1999) discussed, based on 2‐D and 3‐D hybrid simulations, how the core field of flux ropes on the dayside magnetopause and the magnetotail are controlled by the guide field. Teh, Abdullah, and Hasbi (2014) studied the core field of two flux ropes observed at the magnetopause under high magnetic shear. They found that the polarity of the core field of one of the flux ropes is opposite to the guide field produced by reconnection as observed near the flux ropes.…”
Section: Introductionmentioning
confidence: 99%
“…The guide field of the primary reconnection northward of MMS was negative (B y < 0), while the core field (predominantly B y ) in the MFR was positive (Figure 1a). It has been shown that the core field inside a MFR was occasionally opposite to that of the ambient guide field (Eriksson et al., 2016; S. Huang et al., 2014; Teh et al., 2014). A possible explanation is that the core field inside the MFR was originated from the Hall magnetic field.…”
Section: Discussionmentioning
confidence: 99%